Assessment of Water Quality in MARDI (Malaysian Agricultural Research and Development Institute) for Sustainable Farming - Agnes Fitriani Siregar; Alridiwirsah; Mohd Nordin Abdul Rahman (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
This study aims to assess the water quality at MARDI Serdang, Selangor, Malaysia, which is utilized to support MARDI’s efforts in maintaining the availability and quality of water for research purposes and sustainable agricultural activities. This study was conducted to assess the water quality at several selected locations within the Malaysian Agricultural Research and Development Institute (MARDI). Several key physico-chemical parameters such as dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), pH, and the presence of certain heavy metals were analyzed. Water samples were collected from identified sampling points and analyzed according to the standard procedures established by the American Public Health Assiciation (APHA, 2017). The analytical results were compared with the Water Quality Index (WQI) standards used by the Department of Environment (DOE) Malaysia. The findings of the study showed significant variations in water quality among the sampling locations, with some areas exceeding the Class II limits specified in the Malaysian National Water Quality Standars. This study emphasizes the need for continuous monitoring and recommends measures to maintain and improve water quality within MARDI facilities. Overall, this study provides important insights into the water quality conditions at MARDI Serdang. Through regular monitoring and the implementation of approriate water treatment technologies, MARDI can maintain water quality while supporting the implementation of sustainable agriculture in the future.